Mechanism study on the improvement of egg white emulsifying characteristic by ultrasound synergized citral: Physicochemical properties, molecular flexibility, protein structure - Pei Zhang; Lan Liu; Qun Huang; Shugang Li; Fang Geng; Hongbo Song; Fengping An; Xin Li; Yingmei Wu (Ultrasonics Sonochemistry)
As a natural emulsifier, egg white protein (EWP) has great interfacial characteristics and high security, and has broad development prospects. This study explored the impact of ultrasound synergized citral (CI) treatment on the microstructure, molecular flexibility and emulsifying property of EWP, and predicted the interaction between CI and ovalbumin (the main protein in EWP) through molecular docking. The decrease in free amino content and the growth in molecular weight of EWP suggested that CI and proteins were successfully grafted. The results of physicochemical properties revealed that UCEWP (ultrasound synergized citral-treated EWP) had smaller particle size and larger ζ-potential absolute value, which meant that the stability of UCEWP system was enhanced. From the perspective of interfacial characteristics, UCEWP had lower interfacial tension, which remarkably improved its emulsifying property. The emulsifying activity index (EAI) and emulsifying stability index (ESI) of UCEWP were 1.99 times and 3.19 times higher than that of natural EWP (NEWP). Analysis of Fourier transform infrared spectroscopy (FT-IR) and fluorescence spectroscopy illustrated that the secondary and tertiary structures of UCEWP were more disordered and stretched than those of EWPs. Protein microstructure demonstrated that UCEWP presented loose small particle distribution, and correlation analysis reflected that the improvement of molecular flexibility was positively correlated with the enhancement of emulsifying property. These results elucidated that ultrasound synergized CI treatment is an effective mean to improve the molecular flexibility and emulsifying property of EWP, which provides a valuable reference for further application of EWP.